Examining the potential use and long-term stability of guaiac faecal occult blood test cards for microbial DNA 16S rRNA sequencing. Issue 7 (23rd December 2016) - Taylor, Morag; Wood, Henry M; Halloran, Stephen P; Quirke, Philip
Abstract : Aims: With a growing interest in the influence the gut microbiome has on the development of colorectal cancer (CRC), we investigated the feasibility and stability of isolating and typing microbial DNA from guaiac faecal occult blood test (gFOBt) cards. This has the future potential to screen the microbial populations present in confirmed colorectal neoplasia cases with aims to predict the presence and development of CRC. Methods: Fresh stool samples from three healthy volunteers were applied to gFOBt cards. DNA was extracted from both the cards and fresh stool samples. A series of additional cards were prepared from one volunteer, and extracted at time points between 2 weeks and 3 years. The V4 region of the 16S rRNA gene was amplified and sequenced on an Illumina MiSeq at 2×250 bp read lengths. Data were analysed using QIIME software. Results: Samples were grouped both by volunteer and by type (fresh or gFOBt), and compared a variety of ways: visual inspection of taxa, α and β diversity, intraclass correlation. In all comparisons, samples grouped by volunteer, and not by sample type. The different time points showed no appreciable differences with increased storage time. Conclusions: This study has demonstrated that there is good concordance between microbial DNA isolated from fresh stool sample, and from the matched gFOBt card. Samples stored for up to 3 years showed no detrimental effect on measureable microbial DNA. This study has important future implications for investigating microbial influence on CRC development and other pathologies.